By the sword : a Repairman Jack novel - Wilson, F. Paul (Francis Paul) (Wilson, F. Paul (Francis Paul). Repairman Jack novels., 2008)
Hired to find a legendary Japanese sword that had been stolen from the Hiroshima Peace Museum, Jack finds his task complicated by dangerous rivals for the sword and a pregnant teen who is carrying a child of destiny.